Experimental Study on COD Composition and Electrochemical Degradation of Wastewater in Offshore Oilfields. Issue 1 (17th November 2016) - Yang, Mengying; Jing, Bo; Chen, Wenjuan; Li, Qing; Yin, Xianqing
Abstract : Chemical oxygen demand (COD) of standard discharge wastewater in offshore oilfields is an important part of oilfield wastewater treatment. Polymer‐containing oily wastewater from oilfields in Bohai Sea was taken as the subject of this study. Combined with wastewater treatment experiments, the major composition of COD such as oils, polymer, and chemical agents is studied. Under certain conditions, the two‐dimensional plug‐flow electrochemical reactor was used to treat wastewater, and a linear relation between COD and concentration was established in the low concentration range. A preliminary study was carried out on the main factors of COD removal, and the results show that, compared to the polymer, oils are more easily electrolyzed whereas the chemical agents are more difficult to be electrolyzed. The highest COD removal by electrochemical treatment of wastewater was 75.34%, and the residual COD in wastewater was mainly contributed by the chemical agents and polymer that were not degraded completely. Abstract : The total chemical oxygen demand (COD) removal rate is 71–75%, and the changing scope is relatively stable. With the increase in polymer content, oil degrades more easily and contributes to a stable COD removal rate from the total COD removal rate. The contribution of the polymer in the total COD removal rate gradually increases while the contribution of agents decreases, which indicates that the agents become more difficult to be degraded.